Influence of Leadership Behavior on Safety Culture Integration at PT Cipta Kridatama Site PT Borneo Indobara - Priambodo, Yustinus Pramono (PT Inovasi Pratama Internasional, 2025)
This study analyzes the interconnections among transformational leadership, safety culture, and safety behavior at PT Cipta Kridatama Site PT Borneo Indobara, a high-risk mining operation. The research, framed by theoretical views like the Theory of Planned Behavior and Hudson’s Safety Culture Maturity Model, underscores the pivotal role of leadership in cultivating a proactive safety culture and impacting safety behavior. This research aims to assess the direct and indirect impacts of transformational safety leadership on safety behavior, with safety culture serving as a mediating variable. The research used Structural Equation Modeling (SEM) to examine quantitative data obtained from employee surveys, assessing leadership techniques, cultural characteristics, and behavioral results. The results indicate that transformational safety leadership exerts a substantial and robust impact on safety culture, evidenced by a coefficient of 0.923, a t-statistic of 72.438, and an effect size of 5.765. The safety culture markedly affects safety behavior, evidenced by a coefficient of 0.495, a t-statistic of 5.920, and an effect size of 0.180. Transformational safety leadership has a moderate direct influence on safety behavior (coefficient: 0.417, t-statistic: 4.977, effect size: 0.127) in comparison to its effect on safety culture. Moreover, safety culture mediates the connection between transformational leadership and safety behavior, evidenced by a mediation coefficient of 0.457, a t-statistic of 5.863, and an impact size of 0.180, underscoring its crucial function in converting leadership into behavioral results. The research emphasizes the necessity of combining transformational leadership methods with initiatives to foster a strong safety culture. Recommendations involve augmenting leadership training to integrate safety-oriented practices and executing cultural alignment techniques to maintain proactive safety habits. These insights enhance safety management techniques in high-risk sectors, foster safer workplaces, and improve overall operational outcomes.